THE USE OF CHATGPT IN ENGLISH WRITING ACTIVITIES: : STUDENTS’ VOICES - Natasya Aprodi Giani; Ridha Ilma; Hariana Amalia (Didascein : Journal of English Education, 2025)
The rapid development of artificial intelligence has influenced education, including the use of ChatGPT in language learning. ChatGPT can revolutionize many aspects of education, such as retrieving information, responding to specific questions in a variety of subjects, participating in open discussions, writing and editing essays and reports, creating software code, mentoring students by elucidating programming concepts, supplying sample data for databases and analysis, and carrying out computations. This study investigated students’ perceptions of using ChatGPT in English writing activities at the English Education Study Program of UIN Raden Fatah Palembang. A quantitative approach was used with 136 fourth-semester students as the research participants. Data were collected through an open-ended questionnaire focusing on six aspects: ChatGPT usage, impact on writing, reliability and accuracy, contribution to learning goals, user experience and satisfaction, and training needs. The findings showed that most students had a positive view of ChatGPT, especially in brainstorming and organizing ideas. About 91.3% of students had used ChatGPT in class, and 94.9% had prior experience. Although only 8.7% used it regularly, ChatGPT was seen as helpful for improving efficiency, creativity, and confidence. Students also recognized its limitations, such as the necessity of information verification and avoiding over-reliance. The study concludes that ChatGPT can be a valuable tool for academic writing when it is combined with strong digital literacy and ethical use.